2006
DOI: 10.1097/00149831-200606000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and health status in adults with congenital heart disease: a direct comparison with healthy counterparts

Abstract: Adults with congenital heart disease perceived their quality of life to be better than did their healthy counterparts. This finding refutes the presumed lower quality of life in patients with cardiac anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 17 publications
6
135
1
Order By: Relevance
“…Despite the parameters above discussed have been widely employed for late results evaluation of patients followed in the long term, we share the opinion that the individual quality of life is an important aspect which should be considered in the outpatient assessment because it can give a more complete idea of the individual status [12,26].…”
Section: Late Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the parameters above discussed have been widely employed for late results evaluation of patients followed in the long term, we share the opinion that the individual quality of life is an important aspect which should be considered in the outpatient assessment because it can give a more complete idea of the individual status [12,26].…”
Section: Late Resultsmentioning
confidence: 99%
“…The great majority of these patients, however, can not be considered cured. Sequela and residual lesions are frequent [2] demanding special attention during a period of life when problems related to the individual activities and to the natural aging process might interfere with the lesion physiopathology [11,12]. An interesting and still not well discussed subject, especially in Brazil, is the surgical approach in adults with congenital heart disease, frequently necessary in those patients with late diagnosis and those in need of a reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…We measured perceived health using a linear analogue scale (LAS) [12,13] and the Medical Outcome Study, Short-Form 36 (SF-36) [14]. The LAS is a 10-cm-long vertical line divided into a scale ranging from 0 (worst imaginable health status) to 100 (best imaginable health status).…”
Section: Methodsmentioning
confidence: 99%
“…In the literature the evidence for this assumption is mixed. While van Rijen et al (Van Rijen et al 2004;Van Rijen et al 2005b) reported that women were more affected by psychopathological reactions, other studies concluded that the quality of life of CHD-patients in general was comparable with the general population (Immer et al 2007;Moons et al 2006). In our study we found evidence that males suffered considerably more than female patients on a series of psychological measures, in particular anxiety, depression, and hostility.…”
Section: Discussionmentioning
confidence: 97%